231k views
2 votes
3T-2 + T -5T= -1
Solve it out please

User Kleist
by
5.6k points

1 Answer

2 votes

Answer: T = -1

Explanation:

**Disclaimer** I assume that the [T] is a variable. If it was, then you may refer to my answer. If it was not, then you may point it out and I'll redo it.

Given

3T - 2 + T - 5T = -1

Combine like terms

-T - 2 = -1

Add 2 on both sides

-T - 2 + 2 = -1 + 2

-T = 1

Divide -1 on both sides

-T / (-1) = 1 / (-1)

T = -1

Hope this helps!! :)

Please let me know if you have any questions

User Visualspark
by
5.9k points